Elemen-Elemen Organisasi bagi Pengembangan Perguruan Tinggi Swasta di Era Disruptif - Agus Salim Chamidi (LPPM IAINU Kebumen, 2022)
This article aims to find out the elements of the organization and at the same time try to build a model for the development of private universities based on these elements. The article uses descriptive narrative method. The result is that there are 7 elements: strategy, structure, system, shared values, style, staff, and skills. PTS carries out the tri dharma: teaching, research, and community service. The development of private universities relies on the transformative managerial ability of its leadership in the midst of a disruptive global flow.